Assistive technologies and the visually impaired: a digital ecosystem perspective - Calder, David (ACM, 2010)
Assistive technology devices for the visually impaired form a small part of a much wider support infrastructure of people and systems that cluster about a particular disability. Various disabilities, in turn, form part of a greater ecosystem of sometimes isolated support teams. These may cluster about a nucleus of various specific disabilities, such as vision impairment, speech or hearing loss, each focusing on their own particular disability category. Teams are comprised of therapists, caregivers, trainers, as well as device manufacturers, who design and produce computer-based systems such as mobility aids. There is, however, little evidence of any real crossover collaboration or communication between different disability support teams and a disparate cottage industry of manufacturers. The author proposes a collaborative digital ecosystem framework that may assist this challenge. Although this paper is not a survey of all available devices, examples of some commercial systems are cited in order to draw attention to user interface challenges that confront both those who rely on them....and those who design them.